In vitro and ex vivo comparison of reactive oxygen-releasing granules for internal tooth bleaching - Mayer, Romy M.; Gubler, Andrea; Attin, Thomas; Zehnder, Matthias (Frontiers in Dental Medicine, 2024)
Introduction: Traditionally, internal tooth bleaching was performed using sodium perborate slurries. These are banned in some areas for potential carcinogenic effects. More recently, highly concentrated hydrogen peroxide gels have been used, which may cause dentin degradation. Consequently, the search for ideal internal tooth bleaching agents is still on. This study compared pure ROS-releasing granules regarding their liberation of oxidizing species, pH induction, bleaching of blood-stained dentin, and effects on mechanical dentin properties. Materials and methods: The ROS-releasing granules under investigation were sodium perborate, carbamide peroxide, and sodium percarbonate in aqueous suspension (4:3, wt/wt). The bleaching efficacy of these suspensions was compared in blood-stained human dentin (n = 6) ex vivo. In addition, effects on mechanical dentin integrity were tested using bovine dentin beams (n = 9) exposed to a 3-point bending test (ISO 4049) after immersion in test suspensions or control solutions (35% H2O2 and physiological saline) for 1 week. Results: Granules release between 21.5% and 35.2% (wt/wt) of H2O2 equivalent. The sodium-containing granules (perborate and percarbonate) caused an alkaline pH of 10.3 and 10.6, respectively. The carbamide peroxide suspension was acidic (pH 3.9), as was the 35% H2O2 solution used as a control (pH 2.2). All the suspensions bleached the blood-stained dentin, albeit with a lesser overall effect by sodium percarbonate (one-way ANOVA and Tukey's HSD, p < 0.05). The acidic preparations caused a severe (over 50%) reduction in flexural strength of the dentin (p < 0.05 compared to physiological saline solution), while the alkaline counterparts did not. Conclusions: Sodium perborate granules in aqueous suspension combined good de-staining properties with limited untoward effects on dentin integrity. Further studies are required to identify alternative compounds with a lesser general health concern.